(untitled) (Medico Legal Update, 2020)
Background: Acute appendicitis is amongst the most encountered emergencies seen in casualties requiring intervention. The incidence of negative laparotomy is 15% to 25% and is associated with notable morbidity. Scoring systems are useful and logical for distinguishing acute appendicitis from non-specific abdominal pain. Presently many scoring systems exist that aids in the diagnosis of acute appendicitis but still fail to decrease the rates of wrong diagnosis and the negative appendicectomy rate. This study has been undertaken to evaluate the efficacy of the newer Yash scoring system which has been found more effective for the Indian population in diagnosing acute appendicitis. Method and Material: A prospective study of the Yash scoring system was done on 50 patients. The decision of an appendicectomy was taken by the consultant surgeon. The outcomes of the Yash scoring system in terms of sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy were calculated. Results: The Yash scoring system had sensitivity, specificity, PPV, NPV, and DA of 94.28%, 93.33%, 97.05%, 87.50%, and 94% respectively. Conclusion: The Yash scoring system was a good tool to diagnose acute appendicitis.